Child supervision in low- and middle-income countries: A scoping review. (June 2018) - Miconi, Diana; Beeman, Irene; Robert, Emilie; Beatson, Jesse; Ruiz-Casares, Mónica
Abstract: Despite the importance of adequate supervision to child wellbeing, the academic conversation around this topic is scattered across disciplines and for this reason is difficult to follow. Researchers and decision-makers would benefit from a preliminary overview of conceptualizations, cultural variations, and facilitators and barriers to providing supervision to children in low- and middle-income countries (LMICs). A scoping review was conducted. Two searches of the literature were run within Embase, Medline, PsycInfo, Social Sciences Full Text, ERIC, SocIndex with Full Text, and Academic Search Complete. Additional papers were identified through a call to experts. Out of 2049 publications initially identified, 44 studies met our inclusion criteria, thus reflecting the scarcity of scientific evidence in LMICs. Child supervision was addressed in the literature in terms of links to psychological, health, social and academic outcomes, suggesting a multidisciplinary interest in the topic. However, a vague conceptualization of child supervision emerged across studies. Of importance, cultural and socio-economic influences interacted to shape caregivers' vision of the family, the child, and the decision-making process regarding supervision practices. Barriers and/or facilitators to adequate child supervision were addressed only in 18 studies. There was substantial variation in how cultural influences on child supervision were taken into account across studies. Our review aims to inform and guide future research and action on child supervision practices in LMICs and calls for a more coherent and comprehensive body of literature on this matter. Programming and policy efforts should take socio-economic and cultural influences into account, as well as be tailored according to the specificities of each child, caregiver(s), and setting. Highlights: Scant studies investigated child supervision in low- and middle income countries. There is a multi-disciplinary interest on child supervision in LMICs. There is large variation in how cultural influences are considered across studies. Importance of an ecological framework to inform interventions on child supervision A more comprehensive understanding of child supervision across disciplines is needed.